Online webinar: how to build a PC / Nor Hayati Kassim - Kassim, Nor Hayati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
On 26 May 2023, Semester 2 and Semester 4 students from the School of Information Science, College of Computing, Informatic and Mathematic at UiTM Samarahan embarked on a digital adventure by attending the online program “How to Build a PC.” This program was co-organized by three lecturers, Dr Rafiz Salji, Madam Zainon Haji Bibi, and myself, who teach the subjects IMD163 (Computer System Operation) and IMD222 (Technical Support Services and Maintenance for Information Agency). Our goals were to allow students to learn from subject experts.